Prevalence of gastro-intestinal symptoms during pregnancy: a questionnaire based study in a tertiary care center of South Asia - Sharma, J. B.; Karmakar, Debjyoti; Aggarwal, Shena; Singhal, Saurabh; Roy, K. K.; Kumar, S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Gastrointestinal symptoms lead to morbidity in pregnancy, yet remain a surprisingly under-researched topic. The objective was to find out the prevalence of various gastro-intestinal symptoms in pregnant women, the status before pregnancy, and their perceived impact. Methods: A questionnaire incorporating various gastro-intestinal problems was prepared and used over 184 pregnant women to know their prevalence in different trimesters of pregnancy and compare them with prevalence before pregnancy. 184 matched non-pregnant women were also interrogated as additional control group. Results: Constipation was seen significantly more often during pregnancy (24.5%) and was maximum in the first trimester (31.8%) followed by third trimester (26.3%) and second trimester (19.0%) as compared to only 9.8% of women in non-pregnant state. Diarrhea was also more rampant in pregnancy (9.2%), especially in third trimester (13.1%) than before pregnancy (1.6%). Constipation, diarrhea and fecal incontinence were much commoner in pregnant as compared to non-pregnant controls. Conclusions: There is a very high prevalence of gastro-intestinal symptoms during pregnancy as compared to non-pregnant state. More studies are needed to highlight the Quality-Of-Life issues with these symptoms.